Dermatitis herpetiformis: effect of gluten-free diet on skin IgA and jejunal structure and function. Issue 6065 (2nd April 1977) - Harrington, C I; Read, N W
Abstract : To clarify the controversy about the effectiveness of a gluten-free diet in dermatitis herpetiformis, 10 highly motivated patients were investigated. The indices used to assess improvement included deposition of sub-epidermal IgA in unaffected skin, counts of intraepithelial lymphocytes, deposition of IgA in jejunal villi, and electrical tests of glucose absorption. In every patient subepidermal IgA concentrations fell after gluten withdrawal. In all but one patient the dose of dapsone necessary to control symptoms was reduced. Indeed, six patients stopped taking the drug completely within a year. In nine patients biopsy specimens were taken from the jejunum; seven showed abnormalities in jejunal morphology, eight had increased numbers of intraepithelial lymphocytes, and five had increased numbers of IgA-reactive cells in the lamina propria. Two of these three indices improved after gluten withdrawal, which confirmed that all nine patients were adhering to their diet. Routine screening for malabsorption proved to be unsatisfactory for showing the mild jejunal disease found in patients with dermatitis herpetiformis. The electrical test of glucose absorption showed subnormal results in all eight patients tested, however, and in six the results improved after gluten withdrawal.